Researching Quality in Care Transitions : International Perspectives - Aase, Karina; Waring, Justin; Schibevaag, Lene (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book is concerned with the complexities of achieving quality in care transitions. The organization and accomplishment of high quality care transitions relies upon the coordination of multiple professionals, working within and across multiple care processes, settings and organizations, each with their own distinct ways of working, profile of resources, and modes of organizing. In short, care transitions might easily be regarded as complex activities that take place within complex systems, which can make accomplishing high quality care challenging. As a subject of enquiry, care transitions are approached from many research, improvement and policy perspectives: from group psychology and human factors to social and political theory; from applied process re-engineering projects to exploratory ethnographic studies; from large-scale policy innovations to local improvements initiatives. This collection will provide a unique cross-disciplinary and multi-level analysis, where each chapter presents a particular depth of insight and analysis, and together offer a holistic and detail understand of care transitions.
Keywords: Social sciences.; Health care management.; Health services administration.; Quality control.; Reliability.; Industrial safety.; Social medicine.; Social service.; elektronické knihy; electronic books